2017
DOI: 10.1200/jco.2016.70.7091
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative Versus Reduced-Intensity Hematopoietic Cell Transplantation for Acute Myeloid Leukemia and Myelodysplastic Syndromes

Abstract: The optimal regimen intensity before allogeneic hematopoietic cell transplantation (HCT) is unknown. We hypothesized that lower treatment-related mortality (TRM) with reduced-intensity conditioning (RIC) would result in improved overall survival (OS) compared with myeloablative conditioning (MAC). To test this hypothesis, we performed a phase III randomized trial comparing MAC with RIC in patients with acute myeloid leukemia or myelodysplastic syndromes. Patients and MethodsPatients age 18 to 65 years with HCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
421
12
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 541 publications
(470 citation statements)
references
References 33 publications
21
421
12
4
Order By: Relevance
“…This supports the current understanding that allogeneic HCT is likely the best long-term treatment strategy for this highest-risk patient population 28,29 compared with only 10% long-term survival in patients who receive chemotherapy alone. 6 This study indicates that patients who received myeloablative regimens had a lower risk 21 This present study also showed no difference in NRM between the 2 conditioning groups, which is different from many prior retrospective studies in patients with AML/MDS who received allogeneic HCT. [14][15][16][17][18][19][20]30 In the current era of improved supportive care and understanding of management of posttransplantation complications, NRM has overall declined compared with years past, although prospective data still suggest that NRM is generally less in patients who received RICs.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This supports the current understanding that allogeneic HCT is likely the best long-term treatment strategy for this highest-risk patient population 28,29 compared with only 10% long-term survival in patients who receive chemotherapy alone. 6 This study indicates that patients who received myeloablative regimens had a lower risk 21 This present study also showed no difference in NRM between the 2 conditioning groups, which is different from many prior retrospective studies in patients with AML/MDS who received allogeneic HCT. [14][15][16][17][18][19][20]30 In the current era of improved supportive care and understanding of management of posttransplantation complications, NRM has overall declined compared with years past, although prospective data still suggest that NRM is generally less in patients who received RICs.…”
Section: Discussioncontrasting
confidence: 55%
“…Although our study included only patients with sAML with high-risk cytogenetics and active disease going into transplant, which typically is considered a very high-risk group, our cumulative incidence of relapse was not higher than what is typically noted in the literature for this population, regardless of the 21,25 This may suggest that even in these very high-risk patients, long-term survival can be achieved. However, our current knowledge of AML now includes a robust understanding of the importance of molecular data in risk stratification of patients.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Two meta-analyses suggest that RIC may be associated with higher relapse rate (RR) in acute leukemia [5,6]. Furthermore, in the LBA-8 study, which was a prospective randomized trial of MAC (chemotherapy-based or TBI-based) versus RIC regimens for allo-hematopoietic stem cell transplantation (HSCT) for myelodysplastic syndrome (MDS) or AML, RIC resulted in a significant reduction in NRM, whereas MAC resulted in significantly lower RR, higher relapse-free survival (RFS), and a trend toward improved overall survival (OS) [7]. These data support MAC as the preferred approach for those able to tolerate it.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some data suggest that Flu/Mel may be associated with lower RR compared to Flu/Bu, despite both being grouped as RIC regimens [9]. In the LBA-8 study, separate outcomes were not reported for Flu/Mel and Flu/Bu [7]. In studies of MAC versus RIC, results of TBIBC and chemotherapy-based conditioning are often combined; however, patients with AML are increasingly being prepared for allo-HSCT with chemotherapy-based conditioning rather than TBIBC, and review of a large database showed a RFS and OS advantage associated with chemotherapy [10].…”
Section: Introductionmentioning
confidence: 99%